Rice Morphology Determinant-Mediated Actin Filament Organization Contributes to Pollen Tube Growth. Issue 1 (26th March 2018) - Li, Gang; Yang, Xiujuan; Zhang, Xiaoqing; Song, Yu; Liang, Wanqi; Zhang, Dabing
Abstract : RMD, a type II formin, controls pollen tube growth by regulating the direction and distribution of actin filaments arrays in rice (Oryza sativa). Abstract: For successful fertilization in angiosperms, rapid tip growth in pollen tubes delivers the male gamete into the ovules. The actin-binding protein-mediated organization of the actin cytoskeleton within the pollen tube plays a crucial role in this polarized process. However, the mechanism underlying the polarity of the actin filament (F-actin) array and behaviors in pollen tube growth remain largely unknown. Here, we demonstrate that an actin-organizing protein, Rice Morphology Determinant (RMD), a type II formin from rice ( Oryza sativa ), controls pollen tube growth by modulating the polarity and distribution of the F-actin array. The rice rmd mutant exhibits abnormal pollen tube growth and a decreased germination rate of the pollen grain in vitro and in vivo. The rmd pollen tubes display a disorganized F-actin pattern with disrupted apical actin density and shank longitudinal cable direction/arrangement, indicating the novel role of RMD in F-actin polarity during tip growth. Consistent with this role, RMD localizes at the tip of the rice pollen tube, which is essential for pollen tube growth and polarity as well as F-actin organization. Furthermore, the direction and characteristics of the RMD-guided F-actin array positively regulate the deposition of cell wall components and the pattern and velocity of cytoplasmic streaming during rice pollen tube growth. Collectively, our results suggest that RMD is essential for the spatial regulation of pollen tube growth via modulating F-actin organization and array orientation in rice. This work provides insights into tip-focused cell growth and polarity.